Zamknięcie żyły środkowej siatkówki w przebiegu samoistnej przetoki szyjno-jamistej - Kątski, Wojciech; Matysik, Anna; Belniak, Ewa; Szajner, Maciej; Munir, Ali; Wojczal, Joanna (Klinika Oczna / Acta Ophthalmologica Polonica, 2003)
Purpose: This study presents the case history of a 58-year-old woman with a diagnosed spontaneous carotid-cavernous fistula on the left side and mild hypertension. The first signs of this disease were: headache, double vision, proptosis, ptosis of the left upper lid, paresis of the left abducens nerve, conjunctival edema, dilatation and tortuosity of the vessels in conjunctiva and episclera. In the course of this disease a massive central retinal vein occlusion occured in the left eye. The angiography demonstrated carotidcavernous fistula on the left side with pathological blood flow. Embolization of the fistula was attempted, but it was not successful. During 6 months of follow up, the signs of central retinal vein occlusion and other manifestations disappeared. Conclusions: A spontaneous carotid-cavernous fistula should be considered as one of the contributing factors of the central retinal vein occlusion, particulary in menopausal women with concomitant arterial hypertension. The significant reduction of neurological and ophthalmological symptoms and signs may suggest, that arteriovenous shunt is closed.